Silica Nanoparticles—A Versatile Tool for the Treatment of Bacterial Infections - Selvarajan, Vanitha; Obuobi, Sybil; Ee, Pui Lai Rachel (Frontiers in Chemistry, 2020)
The rapid emergence of drug resistance continues to outpace the development of new antibiotics in the treatment of infectious diseases. Conventional therapy is currently limited by drug access issues such as low intracellular drug accumulations, high drug efflux and/or enzymatic degradation. To improve access, targeted delivery using nanocarriers could provide the quantum leap in intracellular drug transport and retention. Silica nanoparticles (SiNPs) with crucial advantages such as large surface area, ease-of-functionalization, and biocompatibility, are one of the most commonly used nanoparticles in drug delivery applications. A porous variant, called the mesoporous silica nanoparticles (MSN), also confers additional amenities such as tunable pore size and volume, leading to high drug loading capacity. In the context of bacterial infections, SiNPs and its variants can act as a powerful tool for the targeted delivery of antimicrobials, potentially reducing the impact of high drug dosage and its side effects. In this review, we will provide an overview of SiNPs synthesis, its structural proficiency which is critical in loading and conjugation of antimicrobials and its role in antimicrobial applications with emphasis on intracellular drug targeting in anti-tuberculosis therapy, nitric oxide delivery, and metal nanocomposites. The role of SiNPs in antibiofilm coatings will also be covered in the context of nosocomial infections and surgical implants.